Xhubleta: A heteroglossic visual space of narratives - Arapi, Dorina (Contemporary Southeastern Europe, 2024)
Xhubleta is a traditional dress of the communities of North Albania. A significant aspectof the dress is the visual language of the embroidered patterns on it, and this paper aimsto address the visual aspect of them. They have been continuously modified, invented,elaborated by women bearers and subject to their subjectivism, thus shaping differentand simultaneous denominations. Comparing the denomination given by the bearerswith those given by non-bearers, it is observed different points of view influenced bycultural context, worldview, and interpretations shaped by present-day ideologiespropagated through mass media and dominant historical narratives. Drawing onBakhtin's concept of heteroglossia and the work of A. Smith, this paper argues that theembroidered patterns in xhubleta cannot be simply interpreted as reflections of ahistorical past, as some non-wearers might wish to interpret them today. Instead, thesepatterns represent heteroglot, multivoiced realities wherein contradictory meanings ofpast and present converge within the xhubleta. The fieldwork was conducted in NorthAlbania from 2019 to 2021. In-depth interviews, quantitative observations, and onlinequestionnaires constituted the primary methods used in the analysis. The fieldwork datawas then compared to ethnographic accounts provided by Albanian ethnologists, andfurther supplemented by artefacts and visual data to enrich the analysis.